Analysis of English Speaking Proficiency of Airline Operational Staff at Indonesia Airasia - Rowiena Sekar Sari; Amiatun Nuryana (Universitas Palangka Raya, 2026)
This study aims to explore the use of English speaking skills by airline operational staff at Indonesia Air Asia at Juanda International Airport, Surabaya. English plays a crucial role in aviation operations, particularly in ensuring effective communication, maintaining service quality, and supporting operational safety in interactions with international passengers, flight crews, and airport stakeholders. This research employed a descriptive qualitative approach to gain an in-depth understanding of how English is used in real operational contexts and how staff perceive its importance in their daily responsibilities. The data were collected from ten airline operational staff members through semi-structured interviews, direct observations, and document analysis. The data were analyzed thematically following the qualitative data analysis model proposed by Matthew B. Miles, A. Michael Huberman, and Johnny Saldaña. The findings indicate that speaking skills are the most frequently used English skills in daily airline operations, especially when handling passenger inquiries, boarding procedures, and operational coordination. However, several challenges were identified, including difficulties in understanding diverse accents, limited aviation-related vocabulary, grammatical inaccuracies, and a lack of confidence in spontaneous communication. The study concludes that continuous and context-based English training programs are necessary to support airline operational staff in improving their communicative competence, particularly speaking skills relevant to aviation operations and international service standards.